Das Öffnen und Teilen von Daten qualitativer Forschung: eine Handreichung - Steinhardt, Isabel; Fischer, Caroline; Heimstädt, Maximilian; Hirsbrunner, Simon David; Ikiz-Akinci, Dilek; Kressin, Lisa; Kretzer, Susanne; Möllenkamp, Andreas; Portzelt, Maike; Rahal, Rima-Maria; Schimmler, Sonja; Wilke, René; et al.

Learning Open Science by doing Open Science. A reflection of a qualitative research project-based seminar - Steinhardt, Isabel (Education for Information)
Openness in science and education is increasing in importance within the digital knowledge society. So far, less attention has been paid to teaching Open Science in bachelor’s degrees or in qualitative methods. Therefore, the aim of this article is to use a seminar example to explore what Open Science practices can be taught in qualitative research and how digital tools can be involved. The seminar focused on the following practices: Open data practices, the practice of using the free and open source tool “Collaborative online Interpretation, the practice of participating, cooperating, collaborating and contributing through participatory technologies and in social (based) networks. To learn Open Science practices, the students were involved in a qualitative research project about “Use of digital technologies for the study and habitus of students”. The study shows the practices of Open Data are easy to teach, whereas the use of free and open source tools and participatory technologies for collaboration, participation, cooperation and contribution is more difficult. In addition, a cultural shift would have to take place within German universities to promote Open Science practices in general.
Keywords: Open Science; Open Education Practices; Library and Information Sciences; Education; Information Systems

CauseNet: Towards a Causality Graph Extracted from the Web - Heindorf, Stefan; Scholten, Yan; Wachsmuth, Henning; Ngonga Ngomo, Axel-Cyrille; Potthast, Martin (Proceedings of the 28th ACM International Conference on Information and Knowledge Management (CIKM 2020))

Forecasting IT Security Vulnerabilities - An Empirical Analysis - Yasasin, Emrah; Prester, Julian; Wagner, Gerit; Schryen, Guido (Computers & Security)
Today, organizations must deal with a plethora of IT security threats and to ensure smooth and uninterrupted business operations, firms are challenged to predict the volume of IT security vulnerabilities and allocate resources for fixing them. This challenge requires decision makers to assess which system or software packages are prone to vulnerabilities, how many post-release vulnerabilities can be expected to occur during a certain period of time, and what impact exploits might have. Substantial research has been dedicated to techniques that analyze source code and detect security vulnerabilities. However, only limited research has focused on forecasting security vulnerabilities that are detected and reported after the release of software. To address this shortcoming, we apply established methodologies which are capable of forecasting events exhibiting specific time series characteristics of security vulnerabilities, i.e., rareness of occurrence, volatility, non-stationarity, and seasonality. Based on a dataset taken from the National Vulnerability Database (NVD), we use the Mean Absolute Error (MAE) and Root Mean Square Error (RMSE) to measure the forecasting accuracy of single, double, and triple exponential smoothing methodologies, Croston's methodology, ARIMA, and a neural network-based approach. We analyze the impact of the applied forecasting methodology on the prediction accuracy with regard to its robustness along the dimensions of the examined system and software package "operating systems", "browsers" and "office solutions" and the applied metrics. To the best of our knowledge, this study is the first to analyze the effect of forecasting methodologies and to apply metrics that are suitable in this context. Our results show that the optimal forecasting methodology depends on the software or system package, as some methodologies perform poorly in the context of IT security vulnerabilities, that absolute metrics can cover the actual prediction error precisely, and that the prediction accuracy is robust within the two applied forecasting-error metrics.

Development of a numerical method for analyzing the robustness of clinching in versatile process chains - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson

All-optical switching of a dye-doped liquid crystal plasmonic metasurface - Atorf, Bernhard; Mühlenbernd, Holger; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Optics Express)

Designing a Geometry Capstone Course for Student Teachers: Bridging the gap between academic mathematics and school mathematics in the case of congruence - Hoffmann, Max; Biehler, Rolf (INDRUM 2020, Université de Carthage, Université de Montpellier, Sep 2020, Cyberspace (virtually from Bizerte), Tunisia)
At Paderborn University, a new 6th semester geometry-course for upper secondary student teachers has been designed and taught by the first author of this paper. To show links between academic mathematics and school mathematics we established so-called interface weeks. These are weeks during a course in which lecture, exercises and homework focus on topics that are related to the normal canon of content but specially chosen for their relevance in school contexts. In this article, we want to present our design for an interface week on the topic of congruence. In order to do so, we first illustrate how so-called interface aspects are used to systematize the mathematical background of the topic, thus giving future mathematics teachers the chance to act professionally. We then show examples of learning activities and first results of the accompanying research.

Skynet oder Slaughterbots. Schwarmintelligenz in Militär, Politik und Populärkultur - Weber, Jutta (Wissenschaft & Frieden 2020-3: Der kranke Planet. Beilage)

Introduction: Technosecurity Cultures - Weber, Jutta (Technosecurity Cultures, Sonderausgabe „Science as Culture“ (Hg.: Jutta Weber/Katrin M. Kämpf))

Interlaboratory study on rheological properties of cement pastes and reference substances: comparability of measurements performed with different rheometers and measurement geometries - Haist, Michael; Link, Julian; Nicia, David; Leinitz, Sarah; Baumert, Christian; von Bronk, Tabea; Cotardo, Dario; Eslami Pirharati, Mahmoud; Fataei, Shirin; Garrecht, Harald; Gehlen, Christoph; Hauschildt, Inga; et al. (Materials and Structures)
This paper presents the results of an interlaboratory study of the rheological properties of cement paste and ultrasound gel as reference substance. The goal was to quantify the comparability and reproducibility of measurements of the Bingham parameters yield stress and plastic viscosity when measured on one specific paste composition and one particular ultrasound gel in different laboratories using different rheometers and measurement geometries. The procedures for both in preparing the cement paste and carrying out the rheological measurements on cement paste and ultrasound gel were carefully defined for all of the study’s participants. Different conversion schemes for comparing the results obtained with the different measurement setups are presented here and critically discussed. The procedure proposed in this paper ensured a reasonable comparability of the results with a coefficient of variation for the yield stress of 27% and for the plastic viscosity of 24%, despite the individual measurement series’ having been performed in different labs with different rheometers and measurement geometries.
Keywords: Rheology; Wall Slip; Slip; apparent slip; suspension; cement; concrete

Absolute Rheological Measurements of Model Suspensions: Influence and Correction of Wall Slip Prevention Measures - Pawelczyk, Sebastian; Kniepkamp, Marieluise; Jesinghausen, Steffen; Schmid, Hans-Joachim (Materials)
Since suspensions (e.g., in food, cement, or cosmetics industries) tend to show wall slip, the application of structured measuring surfaces in rheometers is widespread. Usually, for parallel-plate geometries, the tip-to-tip distance is used for calculation of absolute rheological values, which implies that there is no flow behind this distance. However, several studies show that this is not true. Therefore, the measuring gap needs to be corrected by adding the effective gap extension δ to the prescribed gap height H in order to obtain absolute rheological properties. In this paper, we determine the effective gap extension δ for different structures and fluids (Newtonian, shear thinning, and model suspensions that can be adjusted to the behavior of real fluids) and compare the corrected values to reference data. We observe that for Newtonian fluids a gap- and material-independent correction function can be derived for every measuring system, which is also applicable to suspensions, but not to shear thinning fluids. Since this relation appears to be mainly dependent on the characteristics of flow behaviour, we show that the calibration of structured measuring systems is possible with Newtonian fluids and then can be transferred to suspensions up to a certain particle content.
Keywords: wall slip prevention; effective gap height; parallel-plate system; structured surfaces; model suspensions; cement paste; fresh concrete

TechnoSecuritySociety: Catastrophic Futures, Pre-emptive Security & Mass Surveillance - Weber, Jutta; Nagenborg, Michael (TechnoScienceSociety. Technological Reconfigurations of Science and Society. Sociology of the Sciences Yearbook)

Lucy Suchman - Weber, Jutta; Pentenrieder, Annelie (Technikanthropologie. Handbuch für Wissenschaft und Studium)

Donna Haraway - Weber, Jutta (Technikanthropologie. Handbuch für Wissenschaft und Studium)

MenschMaschine - Weber, Jutta (Technikanthropologie. Handbuch für Wissenschaft und Studium)

Technosecurity Cultures. Special Issue of ‚Science as Culture‘. Vol. 29(1), März 2020 (Science as Culture)

Analoge Klangsynthese zur Vermittlung von Grundkenntnissen der Signalverarbeitung an Studierende nicht-technischer Fachrichtungen - Krumme, Matthias; Webersen, Manuel; Claes, Leander; Webersen, Yvonne (Fortschritte der Akustik - DAGA 2020)

ASSESSING THE FUTURE: METHODS AND CRITERIA - Gräßler, Iris; Thiele, Henrik; Scholle, P. (Proceedings of the DESIGN 2020 16th International Design Conference)
Abstract As time-to-market is getting shorter, customer needs have to be identified as early as possible in product development. Correctly applied, corporate foresight can give a glimpse into the future to anticipate such needs and thus gain a competitive advantage. A support tool to choose the appropriate method of foresight is not available yet. Thus, a literature study on foresight methods in industry is performed and a novel decision support tool is proposed which avoids high entrepreneurial risks. Based on the findings, potentials for future work are identified for different types of methods.

A Scrum Agile Integrated Development Framework - Thiele, Henrik; Weber, Sebastian; Reichwein, Jannik; Bartolo, Joseph A.; Tchana, Yvan; Jimenez, Lucas; Borg, Jonathan C. (Proceedings of the DESIGN 2020 16th International Design Conference, 26. - 29. Okt. 2020)

Lesekompetenz fördern. Ein Manual für das LIFE-Programm zur Stärkung der Zusammenarbeit von Schule und Elternhaus - Bonanati, Sabrina; Greiner, Christian; Gruchel, Nicole; Buhl, Heike M.

Improving scenario-technique by a semi-automatized consistency assessment based on pattern recognition by artificial neural networks - Gräßler, Iris; Scholle, Philipp; Thiele, Henrik (Proceedings of the DESIGN 2020 16th International Design Conference; 26. - 29. Okt. 2020)

Mechatronischer Entwurf eines geregelten Federungssystems für mittelschwere gepanzerte Kettenfahrzeuge - Gense, Alexander

Produkttolerante Automation zellenbasierter Fertigungssysteme - Bertelsmeier, Fabian

On efficiently solvable cases of Quantum k-SAT - Gharibian, Sevag; Aldi, Marco; de Beaudrap, Niel; Saeedi, Seyran (Communications in Mathematical Physics)

Towards a Critical Theory of Communication as Renewal and Update of Marxist Humanism in the Age of Digital Capitalism - Fuchs, Christian (Journal for the Theory of Social Behaviour)

Communicative Socialism/Digital Socialism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Alltagsleben und Alltagskommunikation im Coronavirus-Kapitalismus - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Everyday Life and Everyday Communication in Coronavirus Capitalism - Fuchs, Christian (tripleC: Communication)

The Utopian Internet, Computing, Communication, and Concrete Utopias - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Erich Fromm and the Critical Theory of Communication - Fuchs, Christian (Humanity & Society)

The Ethics of the Digital Commons - Fuchs, Christian (Journal of Media Ethics)

Vida e comunicação cotidianas no capitalism da coronavirus - Fuchs, Christian (MATRIZes)

Chemical and Morphological Transition of Poly(acrylonitrile)/Poly(vinylidene Fluoride) Blend Nanofibers during Oxidative Stabilization and Incipient Carbonization - Wortmann, Martin; Frese, Natalie; Mamun, Al; Trabelsi, Marah; Keil, Waldemar; Büker, Björn; Javed, Ali; Tiemann, Michael; Moritzer, Elmar; Ehrmann, Andrea; Hütten, Andreas; Schmidt, Claudia; et al. (Nanomaterials)
Thermally stabilized and subsequently carbonized nanofibers are a promising material for many technical applications in fields such as tissue engineering or energy storage. They can be obtained from a variety of different polymer precursors via electrospinning. While some methods have been tested for post-carbonization doping of nanofibers with the desired ingredients, very little is known about carbonization of blend nanofibers from two or more polymeric precursors. In this paper, we report on the preparation, thermal treatment and resulting properties of poly(acrylonitrile) (PAN)/poly(vinylidene fluoride) (PVDF) blend nanofibers produced by wire-based electrospinning of binary polymer solutions. Using a wide variety of spectroscopic, microscopic and thermal characterization methods, the chemical and morphological transition during oxidative stabilization (280 °C) and incipient carbonization (500 °C) was thoroughly investigated. Both PAN and PVDF precursor polymers were detected and analyzed qualitatively and quantitatively during all stages of thermal treatment. Compared to pure PAN nanofibers, the blend nanofibers showed increased fiber diameters, strong reduction of undesired morphological changes during oxidative stabilization and increased conductivity after carbonization.

Humidity-Mediated Anisotropic Proton Conductivity through the 1D Channels of Co-MOF-74 - Javed, Ali; Strauss, Ina; Bunzen, Hana; Caro, Jürgen; Tiemann, Michael (Nanomaterials)
Large Co-MOF-74 crystals of a few hundred micrometers were prepared by solvothermal synthesis, and their structure and morphology were characterized by scanning electron microscopy (SEM), IR, and Raman spectroscopy. The hydrothermal stability of the material up to 60 °C at 93% relative humidity was verified by temperature-dependent XRD. Proton conductivity was studied by impedance spectroscopy, using a single crystal. By varying the relative humidity (70–95%), temperature (21–60 °C), and orientation of the crystal relative to the electrical potential, it was found that proton conduction occurs predominantly through the linear, unidirectional (1D) micropore channels of Co-MOF-74, and that water molecules inside the channels are responsible for the proton mobility by a Grotthuss-type mechanism.

A modular, scalable open-hardware platform for project-based laboratory courses in electrical engineering studies - Hetkämper, Tim; Krumme, Matthias; Dreiling, Dmitrij; Claes, Leander (SEFI 48th Annual Conference Proceedings - Engaging Engineering Education)

Online-Lehre 2020 – Eine medienwissenschaftliche Perspektive. Diskussionspapier Nr. 10 - Bohnenkamp, Björn; Burkhardt, Marcus; Grashöfer, Katja; Hlukhovych, Adrianna; Krewani, Angela; Matzner, Tobias; Missomelius, Petra; Raczkowski, Felix; Shnayien, Mary; Weich, Andreas; Wippich, Uwe
Die Autor*innen werfen einen medienwissenschaftlichen Blick auf die Online-Lehre des Sommersemsters 2020. Dabei betrachten sie unter anderem den Unterschied von klassischen Hörsälen zu den neuen, virtuellen Lernräumen, die aber auch physische Elemente beinhalten. Dabei regen sie an, den Einsatz von Lehr-Lern-Plattformen kritisch zu diskutieren und insgesamt die Lehre mit andauernder Medienreflexion zu begleiten. Ein zentraler Punkt des Papiers ist das Aufzeigen von Inklusions- und Exklusionspotenzialen von Online-Lehre. Vermeintliche Selbstverständnisse spielen hier eine Schlüsselrolle. So wird zum Beispiel häufig eine gewisse technische Infrastruktur seitens der Studierenden vorausgesetzt, die nicht immer vorhanden ist. Andererseits entfallen physische Barrieren, die in Lehrgebäuden vorhanden wären. Die Autor*innen mahnen, bei der Konzeption von Online-Lehre zu vermeiden, nicht-behinderte Personen als die Norm anzunehmen und stattdessen von verschiedenen Körperlichkeiten her zu denken, um die positive Potenziale dieses Lehrmodus zu nutzen. Das Diskussionspapier widmet sich auch ausführlich dem Einsatz von (digitalen) Tools, die weniger als Werkzeuge, denn als Medien der Lehre verstanden werden.

Lehre unter besonderen Bedingungen. Leitfaden zur temporären Umstellung der Lehre auf Online-Formate - Heinke, Christian; Shnayien, Mary; Sprenger, Florian; Wippich, Uwe (-)
Die vorübergehende Umstellung der Lehre von Präsenz- auf alternative Formate (sowohl online als auch offline) ist nicht nur eine logistische Herausforderung, sondern hat auch eine medientheoretische und eine wissenschaftspolitische Dimension. Gerade als Medienwissenschaftler_innen sollten wir in dieser Hinsicht reflektiert vorgehen, denn wir haben es mit einer Frage der Übersetzbarkeit von Inhalten zwischen unterschiedlichen Medien zu tun. Der Versuch, Lehrinhalte vom Medium des Sprechens und Diskutierens vor Ort in das Medium etwa einer Konferenzschaltung oder einer kollaborativen schriftlichen Textkommentierung zu übersetzen, verändert diese Inhalte. Wenn wir neue Formate für die Lehre unter besonderen Bedingungen ausprobieren, sollten wir uns die medienwissenschaftliche Prämisse, dass das Medium die Botschaft ist, ständig vor Augen halten. Deshalb schlagen wir vor, diese Aufgabe als ein medienwissenschaftliches Experiment zu betrachten und dieses Experiment im kommenden Semester nicht nur zum Medium, sondern auch zum Inhalt unserer Seminare zu machen.

Explorations in Digital Cultures
Digital media are transformative: they (re)shape the ways of communicating, relating, doing, knowing, and living as much as they are themselves subject to continuous transformation. The contributions in this volume explore these contemporary shifts in and of digital cultures by analyzing a wide range of topics: from data, infrastructures, algorithms, logistics, economies, politics, identities, collectives […] It’s Open Access! Check it out!

Lebenswelten und soziale Netzwerke von jungen Geflüchteten und Zugewanderten am Übergang in Ausbildung und Beruf. - Heisler, Dietmar; Schemmer, Susanne (BWP@ Berufs- und Wirtschaftspädagogik - online)
Jugend wird als eine eigenständige Lebens- und Entwicklungsphase betrachtet. Für junge Geflüchtete stellt sie eine besondere Herausforderung dar. Für sie geht es nicht nur um die Bewältigung alterstypischer Entwicklungsaufgaben, sondern auch um eine gelingende Integration in die Aufnahmegesellschaft. Dazu gehören u. a. das Kennenlernen und die Aneignung von Sprache, Kultur und Werten, genauso die Erschließung von Alltagsräumen und Lebenswelten, z. B. von Freizeitmöglichkeiten, Bildung und von beruflichen Erfahrungsräumen. Die Frage zur gelingenden Integration und Gestaltung von Lebenswelten junger Geflüchteter wurde im Kontext der wissenschaftlichen Begleitung des Projekts „angekommen in Deiner Stadt“ der Walter Blüchert Stiftung genauer untersucht. Der Beitrag referiert u. a. die Ergebnisse einer in diesem Kontext durchgeführten egozentrierten Netzwerkanalyse. Die Ergebnisse zeigen, dass die Angebote den Rahmen für den Aufbau und die Erweiterung kommunikativer, sozialer Netzwerke darstellen und lebensweltliche Zugänge öffnen.
Keywords: Jugend; Lebensweltorientierung; soziale Netzwerke; geflüchtete Jugendliche; Lebenslagen junger Geflüchteter und Zugewanderter

Digitalisierung am Übergang Schule Beruf. Ansätze und Perspektiven in Arbeitsdomänen und beruflicher Förderung

Free and defect-bound (bi)polarons in LiNbO3: Atomic structure and spectroscopic signatures from ab initio calculations - Schmidt, Falko; Kozub, Agnieszka L.; Biktagirov, Timur; Eigner, Christof; Silberhorn, Christine; Schindlmayr, Arno; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)
Polarons in dielectric crystals play a crucial role for applications in integrated electronics and optoelectronics. In this work, we use density-functional theory and Green's function methods to explore the microscopic structure and spectroscopic signatures of electron polarons in lithium niobate (LiNbO3). Total-energy calculations and the comparison of calculated electron paramagnetic resonance data with available measurements reveal the formation of bound polarons at Nb_Li antisite defects with a quasi-Jahn-Teller distorted, tilted configuration. The defect-formation energies further indicate that (bi)polarons may form not only at Nb_Li antisites but also at structures where the antisite Nb atom moves into a neighboring empty oxygen octahedron. Based on these structure models, and on the calculated charge-transition levels and potential-energy barriers, we propose two mechanisms for the optical and thermal splitting of bipolarons, which provide a natural explanation for the reported two-path recombination of bipolarons. Optical-response calculations based on the Bethe-Salpeter equation, in combination with available experimental data and new measurements of the optical absorption spectrum, further corroborate the geometries proposed here for free and defect-bound (bi)polarons.

Communicative Socialism/Digital Socialism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Preface to Manfred Knoche’s Article “Science Communication and Open Access: The Critique of the Political Economy of Capitalist Academic Publishers as Ideology Critique” - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Nanoporous aluminum oxide micropatterns prepared by hydrogel templating - Chen, Zimei; Kuckling, Dirk; Tiemann, Michael (Nanotechnology)
Micropatterned nanoporous aluminum oxide arrays are prepared on silicon wafer substrates by using photopolymerized poly(dimethylacrylamide) hydrogels as porogenic matrices. Hydrogel micropatterns are fabricated by spreading the prepolymer mixture on the substrate, followed by UV photopolymerization through a micropatterned mask. The hydrogel is covalently bonded to the substrate surface. Al2O3 is produced by swelling the hydrogel in a saturated aluminum nitrate solution and subsequent thermal conversion/calcination. As a result, micropatterned porous Al2O3 microdots with heights in µm range and large specific surface areas up to 274 m2 g−1 are obtained. Hence, the hydrogel fulfills a dual templating function, namely micropatterning and nanoporosity generation. The impact of varying the photopolymerization time on the properties of the products is studied. Samples are characterized by light and confocal laser scanning microscopy, scanning electron microscopy, energy-dispersive x-ray spectrometry, and Kr physisorption analysis.

Synthesis of Metal Oxide Inverse Opals from Metal Nitrates by PMMA Colloidal Crystal Templating - Zhang, Xuyang; Weinberger, Christian; Amrehn, Sabrina; Wu, Xia; Tiemann, Michael; Wagner, Thorsten (European Journal of Inorganic Chemistry)
Metal oxide inverse opals are interesting for various applications. To achieve highly ordered inverse opal structures, one important issue during the colloidal crystal templating procedure is to form a stable precursor network before the template loses its structural integrity at high temperature. Using poly(methyl methacrylate), PMMA, colloidal crystal templates, it is essential to consider the physical and chemical changes of the precursors induced by the changes of PMMA during the thermal conversion. For a systematic investigation of this matter, we synthesized a variety of metal oxide inverse opals from the respective metal nitrates, including Cr2O3, Ga2O3, Fe2O3, In2O3, CuO, CeO2, and ZnO, to compare the effect of various modifications of precursors on the structural and optical properties. When the nitrate precursors have a lower thermal stability than the PMMA template, we have modified the metal nitrates by chelating or by polyacrylamide gelation to form more stable precursor networks.

Proton Conduction in a Single Crystal of a Phosphonato‐Sulfonate‐Based Coordination Polymer: Mechanistic Insight - Javed, Ali; Wagner, Thorsten; Wöhlbrandt, Stephan; Stock, Norbert; Tiemann, Michael (ChemPhysChem)
The proton conduction properties of a phosphonato-sulfonate-based coordination polymer are studied by impedance spectroscopy using a single crystal specimen. Two distinct conduction mechanisms are identified. Water-mediated conductance along the crystal surface occurs by mass transport, as evidenced by a high activation energy (0.54 eV). In addition, intrinsic conduction by proton ′hopping′ through the interior of the crystal with a low activation energy (0.31 eV) is observed. This latter conduction is anisotropic with respect to the crystal structure and seems to occur through a channel along the c axis of the orthorhombic crystal. Proton conduction is assumed to be mediated by sulfonate groups and non-coordinating water molecules that are part of the crystal structure.

Functional Nanoporous Materials - Weinberger, Christian; Tiemann, Michael (Nanomaterials)
This Special Issue on “Functional Nanoporous Materials” in the MDPI journal nanomaterials features seven original papers ...

Photocatalytic properties of graphene‐supported titania clusters from density‐functional theory - Badalov, Sabuhi; Wilhelm, René; Schmidt, Wolf Gero (Journal of Computational Chemistry)
Density-functional theory calculations of (TiO2)n clusters (n = 1–5) in the gas phase and adsorbed on pristine graphene as well as graphene quantum dots are presented. The cluster adsorption is found to be dominated by van der Waals forces. The electronic structure and in particular the excitation energies of the bare clusters and the TiO2/graphene composites are found to vary largely in dependence on the size of the respective constituents. This holds in particular for the energy and the spatial localization of the highest occupied and lowest unoccupied molecular orbitals. In addition to a substantial gap narrowing, a pronounced separation of photoexcited electrons and holes is predicted in some instances. This is expected to prolong the lifetime of photoexcited carriers. Altogether, TiO2/graphene composites are predicted to be promising photocatalysts with improved electronic and photocatalytic properties compared to bulk TiO2.

Realization of all-optical vortex switching in exciton-polariton condensates - Meier, Torsten; Ma, Xuekai; Berger, Bernd; Aßmann, Marc; Driben, Rodislav; Schneider, Christian; Höfling, Sven; Schumacher, Stefan (Nature communications)
Vortices are topological objects representing the circular motion of a fluid. With their additional degree of freedom, the vorticity, they have been widely investigated in many physical systems and different materials for fundamental interest and for applications in data storage and information processing. Vortices have also been observed in non-equilibrium exciton-polariton condensates in planar semiconductor microcavities. There they appear spontaneously or can be created and pinned in space using ring-shaped optical excitation profiles. However, using the vortex state for information processing not only requires creation of a vortex but also efficient control over the vortex after its creation. Here we demonstrate a simple approach to control and switch a localized polariton vortex between opposite states. In our scheme, both the optical control of vorticity and its detection through the orbital angular momentum of the emitted light are implemented in a robust and practical manner.

Probability Distribution of Joint Point Loadings in Car Body Structures under Global Bending and Torsion - Martin, Sven; Camberg, Alan A.; Tröster, Thomas (Procedia Manufacturing)

Characterization of Phase Transformations During Graded Thermo-Mechanical Processing of Press-Hardening Sheet Steel 22MnB5 - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Metallurgical and Materials Transactions A)
Abstract Safety-relevant components in automobiles require materials that combine high strength with sufficient residual ductility and high-energy absorption. A graded thermo-mechanical treatment of the press-hardening steel 22MnB5 with graded microstructure can provide a material with such properties. Different austenitization temperatures, cooling and forming conditions within a sheet part lead to the development of microstructures with mixed phase compositions. To determine the resulting phase contents in such graded processed parts, a large number of dilatometric tests are usually required. With a non-contact characterization method, it is possible to detect local phase transformations on an inhomogeneously treated flat steel specimen. For press-hardening steel after heat treatment and thermo-mechanical processing, correlations between austenitization temperature, hot deformation strain, microstructure, and hardness are established.

New Twin-Roll Cast Al-Li Based Alloys for High-Strength Applications - Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko; Belejová, Sára; Králík, Rostislav; Bajtošová, Lucia; Křivská, Barbora; Hájek, Michal; Cieslar, Miroslav (Metals)
Al-Li based alloys are attractive materials for the aerospace industry. The twin-roll casting of such materials could provide properties not achievable by conventional direct-chill casting and downstream processing methods due to significantly higher solidification rates. An Al-Li-Cu-Mg-Zr alloy was twin-roll cast with the same alloy containing a small addition of Sc. The microstructure of as-cast materials and the influence of Sc on the behavior of the alloy at elevated temperatures were studied by means of light and electron microscopy and by resistivity measurements. A fine-grained structure was formed during twin-roll casting, but several surface and internal defects were found on the strips, which should be suppressed by a further adjustment of the casting conditions. The addition of Sc had a positive effect on grain size uniformity and microstructure stabilization at elevated temperatures, as shown by the precipitation of a fine dispersion of coherent Sc- and Zr-containing precipitates.

Estimation of acoustic wave non-linearity in ultrasonic measurement systems - Claes, Leander; Steidl, Carolin; Hetkämper, Tim; Henning, Bernd (arXiv.org)

Gemeinsam Forschung gestalten. Handreichung zu partizipativer Forschung - Lutz, Katharina; Offergeld, Jana; Freymuth, Nina; Arp, Anna Liza

Interaktionen in mathematischen Spielsituationen in Kindertagesstätte und Familie - Meyer, Lena; Tabeling, Laura; Gasteiger, Hedwig; Bruns, Julia (Beiträge zum Mathematikunterricht 2020)

Mathematisches Fachwissen von frühpädagogischen Fachpersonen im Spannungsfeld zwischen Disziplin- und Praxis - Bruns, Julia (Beiträge zum Mathematikunterricht 2020)

Lebenswelten und soziale Netzwerke von jungen Geflüchteten und Zugewanderten am Übergang in Ausbildung und Beruf - Schemmer, Susanne Jutta; Heisler, Dietmar (bwp@Berufs-und Wirtschaftspädagogik – online, (24.06.2020))

On the multi-domain compact finite difference relaxation method for high dimensional chaos: The nine-dimensional Lorenz system - Kouagou, N.J.; Dlamini, P.G.; Simelane, S.M. (Alexandria Engineering Journal)
In this paper, we implement the multidomain compact finite difference method to numerically study high dimensional chaos by considering the nine-dimensional Lorenz system. Most of the existing numerical methods converge slowly for this kind of problems and this results in inaccurate approximations. Though highly accurate, the compact finite difference method becomes less accurate for problems characterized by chaotic solutions, even with an increase in the number of grid points. As a result, in this work, we adopt the multidomain approach. This approach remarkably improves the results as well as the efficiency of the method.
Keywords: Multidomain; Compact finite difference; 9D Lorenz system

Präpositionen und Deutsch als Fremdsprache: Quantitative Fallstudien im Lernerkorpus MERLIN - Weber, Tassja
Die Dissertation beschäftigt sich mit dem Gebrauch von Präpositionen (z. B. an, für) und Präpositionalphrasen (z. B. an der Wand, für dich) durch Lernende des Deutschen als Fremdsprache (DaF). Es wird untersucht, welche ausgewählten Variablen den Gebrauch dieser Strukturen beeinflussen. Der Schwerpunkt liegt dabei auf Gebrauchsschwierigkeiten. Auf Basis lernersprachlicher Daten im digitalen, frei verfügbaren Lernerkorpus MERLIN (merlin-platform.eu) und unter Berücksichtigung grundlegender Annahmen aktueller Spracherwerbstheorien werden quantitativ ausgerichtete Fallstudien zu folgenden Einflussvariablen durchgeführt: Die Erstsprache der Lernenden, die Sprachkompetenz, die syntaktische Funktion der PP und der semantische Gehalt der Präposition. Die Arbeit bettet sich ein in die Lernerkorpusforschung an der Schnittstelle zur Zweit- und Fremdspracherwerbsforschung. Die Ergebnisse zeigen insgesamt für alle Einflussvariablen einen Effekt und bestätigen damit den Einfluss intralingualer sowie interlingualer Merkmale im Sprachgebrauch von Lernenden. Dabei wird deutlich, dass die Gebrauchsschwierigkeiten nicht quantitativer (Korrektheit), sondern eher qualitativer Natur (Fehlertypen) sind. Die Dissertation liefert empirisch fundierte Erkenntnisse zu Schwierigkeiten im Gebrauch von Präpositionen und PP durch DaF-Lernende, für die bisher systematische, korpusgestützte Untersuchungen fehlten. Die Arbeit zeigt dabei exemplarisch auf, wie Annahmen aus der Spracherwerbsforschung anhand von Lernerkorpusdaten überprüft und mögliche Einflussvariablen im Sprachgebrauch ermittelt werden können. Die Erkenntnisse sind auch für andere Forschungsfelder (u.a. Fremdsprachenunterricht und maschinelle Sprachverarbeitung) relevant.
Keywords: Deutsch als Fremdsprache; Korpuslinguistik; Lernerkorpora; Präpositionen; Präpositionalphrasen; Grammatik; Regressionsanalyse

CP2K: An electronic structure and molecular dynamics software package - Quickstep: Efficient and accurate electronic structure calculations - Kühne, Thomas; Iannuzzi, Marcella; Ben, Mauro Del; Rybkin, Vladimir V.; Seewald, Patrick; Stein, Frederick; Laino, Teodoro; Khaliullin, Rustam Z.; Schütt, Ole; Schiffmann, Florian; Golze, Dorothea; Wilhelm, Jan; et al. (The Journal of Chemical Physics)
CP2K is an open source electronic structure and molecular dynamics software package to perform atomistic simulations of solid-state, liquid, molecular, and biological systems. It is especially aimed at massively parallel and linear-scaling electronic structure methods and state-of-theart ab initio molecular dynamics simulations. Excellent performance for electronic structure calculations is achieved using novel algorithms implemented for modern high-performance computing systems. This review revisits the main capabilities of CP2K to perform efficient and accurate electronic structure simulations. The emphasis is put on density functional theory and multiple post–Hartree–Fock methods using the Gaussian and plane wave approach and its augmented all-electron extension.

Accurate Sampling with Noisy Forces from Approximate Computing - Rengaraj, Varadarajan; Lass, Michael; Plessl, Christian; Kühne, Thomas (Computation)
In scientific computing, the acceleration of atomistic computer simulations by means of custom hardware is finding ever-growing application. A major limitation, however, is that the high efficiency in terms of performance and low power consumption entails the massive usage of low precision computing units. Here, based on the approximate computing paradigm, we present an algorithmic method to compensate for numerical inaccuracies due to low accuracy arithmetic operations rigorously, yet still obtaining exact expectation values using a properly modified Langevin-type equation.

Oracle complexity classes and local measurements on physical Hamiltonians - Gharibian, Sevag; Piddock, Stephen; Yirka, Justin (Proceedings of the 37th Symposium on Theoretical Aspects of Computer Science (STACS 2020))
The canonical problem for the class Quantum Merlin-Arthur (QMA) is that of estimating ground state energies of local Hamiltonians. Perhaps surprisingly, [Ambainis, CCC 2014] showed that the related, but arguably more natural, problem of simulating local measurements on ground states of local Hamiltonians (APX-SIM) is likely harder than QMA. Indeed, [Ambainis, CCC 2014] showed that APX-SIM is P^QMA[log]-complete, for P^QMA[log] the class of languages decidable by a P machine making a logarithmic number of adaptive queries to a QMA oracle. In this work, we show that APX-SIM is P^QMA[log]-complete even when restricted to more physical Hamiltonians, obtaining as intermediate steps a variety of related complexity-theoretic results. We first give a sequence of results which together yield P^QMA[log]-hardness for APX-SIM on well-motivated Hamiltonians: (1) We show that for NP, StoqMA, and QMA oracles, a logarithmic number of adaptive queries is equivalent to polynomially many parallel queries. These equalities simplify the proofs of our subsequent results. (2) Next, we show that the hardness of APX-SIM is preserved under Hamiltonian simulations (a la [Cubitt, Montanaro, Piddock, 2017]). As a byproduct, we obtain a full complexity classification of APX-SIM, showing it is complete for P, P^||NP, P^||StoqMA, or P^||QMA depending on the Hamiltonians employed. (3) Leveraging the above, we show that APX-SIM is P^QMA[log]-complete for any family of Hamiltonians which can efficiently simulate spatially sparse Hamiltonians, including physically motivated models such as the 2D Heisenberg model. Our second focus considers 1D systems: We show that APX-SIM remains P^QMA[log]-complete even for local Hamiltonians on a 1D line of 8-dimensional qudits. This uses a number of ideas from above, along with replacing the "query Hamiltonian" of [Ambainis, CCC 2014] with a new "sifter" construction.

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

End-to-End Training of Time Domain Audio Separation and Recognition - von Neumann, Thilo; Kinoshita, Keisuke; Drude, Lukas; Boeddeker, Christoph; Delcroix, Marc; Nakatani, Tomohiro; Haeb-Umbach, Reinhold (ICASSP 2020 - 2020 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
The rising interest in single-channel multi-speaker speech separation sparked development of End-to-End (E2E) approaches to multispeaker speech recognition. However, up until now, state-of-theart neural network–based time domain source separation has not yet been combined with E2E speech recognition. We here demonstrate how to combine a separation module based on a Convolutional Time domain Audio Separation Network (Conv-TasNet) with an E2E speech recognizer and how to train such a model jointly by distributing it over multiple GPUs or by approximating truncated back-propagation for the convolutional front-end. To put this work into perspective and illustrate the complexity of the design space, we provide a compact overview of single-channel multi-speaker recognition systems. Our experiments show a word error rate of 11.0% on WSJ0-2mix and indicate that our joint time domain model can yield substantial improvements over cascade DNN-HMM and monolithic E2E frequency domain systems proposed so far.

Multi-Talker ASR for an Unknown Number of Sources: Joint Training of Source Counting, Separation and ASR - von Neumann, Thilo; Boeddeker, Christoph; Drude, Lukas; Kinoshita, Keisuke; Delcroix, Marc; Nakatani, Tomohiro; Haeb-Umbach, Reinhold (Proc. Interspeech 2020)
Most approaches to multi-talker overlapped speech separation and recognition assume that the number of simultaneously active speakers is given, but in realistic situations, it is typically unknown. To cope with this, we extend an iterative speech extraction system with mechanisms to count the number of sources and combine it with a single-talker speech recognizer to form the first end-to-end multi-talker automatic speech recognition system for an unknown number of active speakers. Our experiments show very promising performance in counting accuracy, source separation and speech recognition on simulated clean mixtures from WSJ0-2mix and WSJ0-3mix. Among others, we set a new state-of-the-art word error rate on the WSJ0-2mix database. Furthermore, our system generalizes well to a larger number of speakers than it ever saw during training, as shown in experiments with the WSJ0-4mix database.

Gedenken an Luftangriffe auf Paderborn: "Erinnerung wird nie obsolet sein" - Hartung, Olaf (Neue Westfälische)

Deep Neural Network based Distance Estimation for Geometry Calibration in Acoustic Sensor Network - Gburrek, Tobias; Schmalenstroeer, Joerg; Brendel, Andreas; Kellermann, Walter; Haeb-Umbach, Reinhold (European Signal Processing Conference (EUSIPCO))
We present an approach to deep neural network based (DNN-based) distance estimation in reverberant rooms for supporting geometry calibration tasks in wireless acoustic sensor networks. Signal diffuseness information from acoustic signals is aggregated via the coherent-to-diffuse power ratio to obtain a distance-related feature, which is mapped to a source-to-microphone distance estimate by means of a DNN. This information is then combined with direction-of-arrival estimates from compact microphone arrays to infer the geometry of the sensor network. Unlike many other approaches to geometry calibration, the proposed scheme does only require that the sampling clocks of the sensor nodes are roughly synchronized. In simulations we show that the proposed DNN-based distance estimator generalizes to unseen acoustic environments and that precise estimates of the sensor node positions are obtained.

Multi-Path RNN for Hierarchical Modeling of Long Sequential Data and its Application to Speaker Stream Separation - Kinoshita, Keisuke; von Neumann, Thilo; Delcroix, Marc; Nakatani, Tomohiro; Haeb-Umbach, Reinhold (Proc. Interspeech 2020)
Recently, the source separation performance was greatly improved by time-domain audio source separation based on dual-path recurrent neural network (DPRNN). DPRNN is a simple but effective model for a long sequential data. While DPRNN is quite efficient in modeling a sequential data of the length of an utterance, i.e., about 5 to 10 second data, it is harder to apply it to longer sequences such as whole conversations consisting of multiple utterances. It is simply because, in such a case, the number of time steps consumed by its internal module called inter-chunk RNN becomes extremely large. To mitigate this problem, this paper proposes a multi-path RNN (MPRNN), a generalized version of DPRNN, that models the input data in a hierarchical manner. In the MPRNN framework, the input data is represented at several (>_ 3) time-resolutions, each of which is modeled by a specific RNN sub-module. For example, the RNN sub-module that deals with the finest resolution may model temporal relationship only within a phoneme, while the RNN sub-module handling the most coarse resolution may capture only the relationship between utterances such as speaker information. We perform experiments using simulated dialogue-like mixtures and show that MPRNN has greater model capacity, and it outperforms the current state-of-the-art DPRNN framework especially in online processing scenarios.

Diskriminierung begegnen – Vielfalt gestalten : Veranstaltungsreihe von und für Studierende und Interessierte - Treder, Alexandra

Mit Methoden der Drama- und Erzählpädagogik Fremdsprachen lernen - Meyberg, Sora; Treder, Alexandra

Forward-Backward Convolutional Recurrent Neural Networks and Tag-Conditioned Convolutional Neural Networks for Weakly Labeled Semi-Supervised Sound Event Detection - Ebbers, Janek; Haeb-Umbach, Reinhold (Proceedings of the Detection and Classification of Acoustic Scenes and Events 2020 Workshop (DCASE2020))
In this paper we present our system for the detection and classification of acoustic scenes and events (DCASE) 2020 Challenge Task 4: Sound event detection and separation in domestic environments. We introduce two new models: the forward-backward convolutional recurrent neural network (FBCRNN) and the tag-conditioned convolutional neural network (CNN). The FBCRNN employs two recurrent neural network (RNN) classifiers sharing the same CNN for preprocessing. With one RNN processing a recording in forward direction and the other in backward direction, the two networks are trained to jointly predict audio tags, i.e., weak labels, at each time step within a recording, given that at each time step they have jointly processed the whole recording. The proposed training encourages the classifiers to tag events as soon as possible. Therefore, after training, the networks can be applied to shorter audio segments of, e.g., 200ms, allowing sound event detection (SED). Further, we propose a tag-conditioned CNN to complement SED. It is trained to predict strong labels while using (predicted) tags, i.e., weak labels, as additional input. For training pseudo strong labels from a FBCRNN ensemble are used. The presented system scored the fourth and third place in the systems and teams rankings, respectively. Subsequent improvements allow our system to even outperform the challenge baseline and winner systems in average by, respectively, 18.0% and 2.2% event-based F1-score on the validation set. Source code is publicly available at https://github.com/fgnt/pb_sed.

One app to trace them all? Examining app specifications for mass acceptance of contact-tracing apps - Trang, S.; Trenz, M.; Weiger, W.; Tarafdar, M.; Cheung, C. (European Journal of Information Systems)

Geschichte(n) der deutschen Migrationsgesellschaft. Jugendliche erzählen begründete historische Geschichten Eine Unterrichtsreihe für das Portal Zwischentöne.info - Fastlabend-Vargas, Daniel

"Die Bombardierung von Brüssel - teil 1" (PODCAST) - Huybrechts, Yves

"Ein Gespräch mit Guy Vanhengel - Ein Gespräch mit dem Vizepräsidenten des Brüsseler Parlaments, in zwei Teilen." (VIDEO) - Huybrechts, Yves

Interview zur Ausstellung "Rubens und der Barock im Norden" - 2 Teile (VIDEO) - Huybrechts, Yves

Medienpädagogik und Hochschuldidaktik - Neiske, Iris; Bücker, Diana (Medienpädagogik als Schlüsseldisziplin in einer mediatisierten Welt. Perspektiven aus Theorie, Empirie und Praxis 37)

Profession und Disziplin. Ein Schreibgespräch über den Weg durch die Fächer, Schreibdidaktik als Feldforschung (und - nebenbei - die Rettung der Schriftkultur). - Karsten, Andrea; Weisberg, Jan (JoSch - Journal der Schreibwissenschaft)

Aushandlungsprozesse über Freiheiten und Grenzen im selbstregulierten Lernen. Erwartungen und Handlungsmuster bei Schüler*innen und Lehrpersonen im Übergangssystem - Daniel-Söltenfuß, Desiree (bwp@)

Don't patronize me! An experiment on preferences for authorship - Lübbecke, Silvia; Schnedler, Wendelin (Journal of Economics & Management Strategy)

Philosophie und Ethik in der Lehrerinnen und Lehrerbildung - Albus, Vanessa (Handbuch Lehrerinnen- und Lehrerbildung)

“D’Holbach on (Dis-)Esteeming Talent.” - Blank, Andreas (Journal of Modern Philosophy)

“Leibniz: sobre las presunciones y la simplicidad cognitiva” - Blank, Andreas (Tópicos. Revista de filosofía de la Universidad de Santa Fe)

“Helvétius’s Challenge: Moral Luck, Political Constitutions and the Economy of Esteem.” - Blank, Andreas (European Journal of Philosophy)

Neither demarcation nor confrontation. Finding a critical position towards right-wing populism - Haker, Christoph; Otterspeer, Lukas (Zeitschrift für Weiterbildungsforschung)
Abstract Right-wing populism has strongly polarizing effects in politics, education and science—a problem which this article aims to adress. Instead of claiming a demarcation between science and education on the one hand and right-wing populist ideology on the other, we initially focus on continuities. At the same time, we are concerned with finding a critical distance towards right-wing populism. Using the theoretical framework of boundary-work we therefore analyse a case of right-wing populist educational and scientific efforts. Boundary-work can occur in an institutional, content-related and epistemic dimension. While we identify strong continuities in the institutional and content-related dimensions, we see the main difference in the epistemic dimension. In conclusion, we use the results of our analysis to develop a critical position as scientists and educationists towards right-wing populism, drawing consequences for the epistemic, content-related and institutional dimensions.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Right-Wing Populism and Educational Research. Exploring theoretical and methodological perspectives - Haker, Christoph; Otterspeer, Lukas (Zeitschrift für Diskursforschung)

Zum praktischen Nutzen von Theorie. Ein Dialog über die Grenzen von Bildungspraxis, Erziehungswissenschaft und Soziologie - Haker, Christoph; Otterspeer, Lukas (Debatte. Beiträge zur Erwachsenenbildung)
Frank Beier, Franziska Wyßuwa und Elisa Wagner diskutieren in ihrem aktuellen Beitrag Fallinterpretationen zwischen Theorieund Anwendungsbezug den praktischen Nutzen wissenschaftlicher Erkenntnisse, insbesondere von Theorie, für die Schule und Erwachsenenbildung. Wir greifen ihre Position in einer dialogischen Replik kritisch auf. Die Form des Dialogs bietet uns die Möglichkeit, unsere Perspektiven als Erziehungswissenschaftler, Lehrer und Soziologe in die Debatte einzubringen. Wir möchten so die eingespielten Grenzziehungen in ‚Theorie- Praxis-Debatten‘ irritieren und Beiers, Wyßuwas und Wagners Plädoyer für die Stärke wissenschaftlicher Theorie ergänzen. Diese Stärke kommt weniger zur Geltung, wenn Theorie Kontingenz schließende und mehr, wenn sie Kontingenz öffnende Effekte hat. Zudem sollte Theorie nicht auf Modelle oder auf Theorien begrenzter Reichweite beschränkt und die konkrete Verwendung von Theorie zum Gegenstand der (Selbst)Reflexion und (Selbst)Kritik werden.
Keywords: Rehabilitation; Physical Therapy; Sports Therapy and Rehabilitation; General Medicine

Teoría de sistemas crítica y teoría crítica de sistemas sociales: Alegato por una distinción necesaria - Alvear, Rafael; Haker, Christoph (MAD)

Brückenschläge zwischen Musikwissenschaft und Informatik. Theoretische und praktische Aspekte der Kooperation

Brückenschläge zwischen Musikwissenschaft und Informatik – Vorbemerkung - Münzmay, Andreas; Aquavella-Rauch, Stefanie; Veit, Joachim (Brückenschläge zwischen Musikwissenschaft und Informatik. Theoretische und praktische Aspekte der Kooperation)

NFDI4Culture - Consortium for research data on material and immaterial cultural heritage - Altenhöner, Reinhard; Blümel, Ina; Boehm, Franziska; Bove, Jens; Bicher, Katrin; Bracht, Christian; Brand, Ortrun; Dieckmann, Lisa; Effinger, Maria; Hagener, Malte; Hammes, Andrea; Heller, Lambert; et al. (Research Ideas and Outcomes)
Digital data on tangible and intangible cultural assets is an essential part of daily life, communication and experience. It has a lasting influence on the perception of cultural identity as well as on the interactions between research, the cultural economy and society. Throughout the last three decades, many cultural heritage institutions have contributed a wealth of digital representations of cultural assets (2D digital reproductions of paintings, sheet music, 3D digital models of sculptures, monuments, rooms, buildings), audio-visual data (music, film, stage performances), and procedural research data such as encoding and annotation formats. The long-term preservation and FAIR availability of research data from the cultural heritage domain is fundamentally important, not only for future academic success in the humanities but also for the cultural identity of individuals and society as a whole. Up to now, no coordinated effort for professional research data management on a national level exists in Germany. NFDI4Culture aims to fill this gap and create a user-centered, research-driven infrastructure that will cover a broad range of research domains from musicology, art history and architecture to performance, theatre, film, and media studies. The research landscape addressed by the consortium is characterized by strong institutional differentiation. Research units in the consortium's community of interest comprise university institutes, art colleges, academies, galleries, libraries, archives and museums. This diverse landscape is also characterized by an abundance of research objects, methodologies and a great potential for data-driven research. In a unique effort carried out by the applicant and co-applicants of this proposal and ten academic societies, this community is interconnected for the first time through a federated approach that is ideally suited to the needs of the participating researchers. To promote collaboration within the NFDI, to share knowledge and technology and to provide extensive support for its users have been the guiding principles of the consortium from the beginning and will be at the heart of all workflows and decision-making processes. Thanks to these principles, NFDI4Culture has gathered strong support ranging from individual researchers to high-level cultural heritage organizations such as the UNESCO, the International Council of Museums, the Open Knowledge Foundation and Wikimedia. On this basis, NFDI4Culture will take innovative measures that promote a cultural change towards a more reflective and sustainable handling of research data and at the same time boost qualification and professionalization in data-driven research in the domain of cultural heritage. This will create a long-lasting impact on science, cultural economy and society as a whole.
Keywords: Research Data Management

Algebraically Independent Generators for the Algebra of Invariant Differential Operators on SLn(ℝ)/SOn(ℝ) - Hilgert, Joachim; Brennecken, D.; Ciardo, L.

Schule in Zeiten der Pandemie. Empfehlungen für die Gestaltung des Schuljahres 2020/21. Stellungnahme der Expert*innenkommission der Friedrich-Ebert-Stiftung - Maaz, Kai; Jungkamp, Burkhard; Antony, Johanna; Becker-Mrotzek, Michael; Chapman, Azalea; Diedrich, Martina; Eger, Joanna; Eickelmann, Birgit; Hanschmann, Felix; Hebborn, Klaus; Heinrich, Martin; Iscan-Pilic, Gülay; et al.

Die Geschichte des Potsdamer Rechenzentrums: Sozialistische Computernutzung und die Digitalisierung in Ostdeutschland - Schmitt, Martin

Behavior of tall masonry chimneys under wind loadings using CFD technique - Dawood, Abbas O.; Al-Lami, Abbas Jarullah Sangoor; Al-Rkaby, Alaa H.J. (Case Studies in Construction Materials)

Überlegungen auf dem Weg zu einer Theorie lehrbezogenen Wandels an Hochschulen - Jenert, Tobias (Zeitschrift für Hochschulentwicklung)

Professional Development of Vocational Teachers in Language-Sensitive Content Teaching–A Study Visit Abroad as Design-Based Research Intervention for Vocational Teachers Working in School-to-Work Transition Phases - Peitz, Nina-Madeleine

Migration und Mehrsprachigkeit zum Unterrichtsthema machen – Migrationsliteratur als Zugang im Deutschunterricht? - Büttner, Denise; Roll, Heike (ProDaz-Journal)

Erhebung der experimentellen Performanz (Physik-)Studierender - Bauer, Anna; Reinhold, Peter; Sacher, Marc (Naturwissenschaftliche Bildung als Grundlage für berufliche und gesellschaftliche Teilhabe)

Symplectic integration of PDEs using Clebsch variables - McLachlan, Robert I; Offen, Christian; Tapley, Benjamin K (Journal of Computational Dynamics)
Many PDEs (Burgers' equation, KdV, Camassa-Holm, Euler's fluid equations, …) can be formulated as infinite-dimensional Lie-Poisson systems. These are Hamiltonian systems on manifolds equipped with Poisson brackets. The Poisson structure is connected to conservation properties and other geometric features of solutions to the PDE and, therefore, of great interest for numerical integration. For the example of Burgers' equations and related PDEs we use Clebsch variables to lift the original system to a collective Hamiltonian system on a symplectic manifold whose structure is related to the original Lie-Poisson structure. On the collective Hamiltonian system a symplectic integrator can be applied. Our numerical examples show excellent conservation properties and indicate that the disadvantage of an increased phase-space dimension can be outweighed by the advantage of symplectic integration.